1998
DOI: 10.1016/s0014-5793(98)01336-2
|View full text |Cite
|
Sign up to set email alerts
|

An innovative sandwich ELISA system based on an antibody cocktail for gluten analysis

Abstract: A cocktail sandwich ELISA based on the employ of two monoclonal antibodies (MAbs) as coating antibodies and a third MAb conjugated to horseradish peroxidase has been developed for the analysis of gluten in foods. Given that each MAb displays a wide specificity spectrum for wheat, barley, rye and oats prolamins, their combination for ELISA ensures a high crossreactivity with most of the potentially toxic gliadin, hordein, secalin and avenin protein family. One of the unprecedented features of the cocktail sandw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
43
0

Year Published

2001
2001
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 73 publications
(46 citation statements)
references
References 20 publications
2
43
0
Order By: Relevance
“…It may be impossible to accurately measure the prolamin concentration by immunologic methods because of the complex nature of prolamins and the resulting differences in their antibody specificities. Nevertheless, Sorell et al have reported an ELISA system that could recognize barley prolamins to the same extent as wheat prolamins 16 . That antibody cocktail ELISA was developed to analyze food samples with a low prolamin content.…”
Section: Resultsmentioning
confidence: 99%
“…It may be impossible to accurately measure the prolamin concentration by immunologic methods because of the complex nature of prolamins and the resulting differences in their antibody specificities. Nevertheless, Sorell et al have reported an ELISA system that could recognize barley prolamins to the same extent as wheat prolamins 16 . That antibody cocktail ELISA was developed to analyze food samples with a low prolamin content.…”
Section: Resultsmentioning
confidence: 99%
“…For this purpose immunochemical assays and non-immune methods have been introduced (Skerritt and Hill, 1991;Sorell et al, 1998;Denery-Papini et al, 1999). Sensitivity, specificity and reproducibility of most earlier methods for gluten analysis have been unsatisfactory (Stern et al, 2001).…”
Section: Methodology Of Gluten Analysismentioning
confidence: 99%
“…Data on extractability, sensitivity and limit of detection (1.5 mg/kg), on robustness and reproducibility of this test system are promising. The assay is based on a monoclonal antibody reacting with QQPFP residues (Sorell et al, 1998;Valdés et al, 2003). This system is solving problems of standardisation and accuracy in gluten analysis particularly in the relevant low level range.…”
Section: Methodology Of Gluten Analysismentioning
confidence: 99%
“…Moreover, some gluten proteins are known to be toxic to patients with celiac disease (gluten-sensitive enteropathy), the most common food-sensitive enteropathy in humans. [9][10][11][12][13][14] Gluten proteins constitute a special group of cereal proteins where the particular subgroups are structurally and chemically related which makes their analysis quite challenging. Although several analytical techniques such as isoelectric focusing (IEF), one-dimensional sodium dodecyl sulfate (1-D SDS) PAGE and reversedphase high-performance liquid chromatography (RP-HPLC) have been used for the analyses of gluten proteins, there is still demand for a reliable and sensitive method able to identify these proteins unambiguously.…”
mentioning
confidence: 99%
“…3,9,15,16 Several immunological methods such as immunoblotting and enzymelinked immunosorbent assay (ELISA) are commonly applied to quantify gluten proteins in food. 14 25 Proteomic analysis of proteins from barley grains involving gel electrophoresis, mass spectrometry and bioinformatics was first undertaken by Chmelík et al 23,24 Trypsin is the enzyme of choice in most proteomic studies due to its reliability and specificity. However, in the case of cereal storage proteins this enzyme failed.…”
mentioning
confidence: 99%